ANALYSIS OF THE EFFECT OF LEAD TIME ON CUSTOMER SATISFACTION ON THE MARKETPLACE PLATFORM - Zulki Zulkifli Noor (Jurnal Ekonomi, 2023)
E-commerce (electronic commerce) is a business process that connects companies, consumers, and society in the activity of exchanging or selling goods or services and information through electronic transactions. The success of the electronic commerce system in Indonesia stems from the enthusiasm of people who want a practical shopping. If in the past distance and time were obstacles to the relationship between buyers and sellers, the existence of an online buying and selling system can make it easier for people to purchase goods and services because it can be accessed anywhere without limited time. With various benefits and flexibility offered, online shopping is now increasingly favored by the people of Indonesia. Through this research to determine the effect of lead time on customer satisfaction.